Characterization of MOSFET-like carbon nanotube field effect transistor - Hashim, Abdul Manaf (2007)
The downscaling of metal-oxide-semiconductor field-effect transistor (MOSFET) has been taking place since decades ago for enhancing circuit functionality and also for extending Moore’s Law. As the downsizing of MOSFET continues, it faces the challenge of size limitation and severe short-channel effects (SCEs) appear to affect the performance of nanoscale-MOSFET. Some novel nanoelectronic devices are proposed, hoping to overcome those MOSFET limitations. One of the novel nanoelectronic devices is carbon nanotube field-effect transistor (CNFET). Simulation work using MATLAB based programming on CNFET is carried out in this paper to investigate the dependence of current-voltage (I-V) characteristics on various carbon nanotube (CNT) diameters, insulator thicknesses and temperatures as well as their transconductances, gate delays and energy delay products (EDPs). The simulation results are presented and then compared with conventional nanoscale-MOSFET. From the simulated results, CNFET seem to provide better performance than MOSFET in term of high speed capability and lower switching power consumptio